2018
DOI: 10.1186/s12931-018-0736-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired diversity of the lung microbiome predicts progression of idiopathic pulmonary fibrosis

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is the most frequent and severe form of idiopathic interstitial pneumonias. Although IPF has not been thought to be associated with bacterial communities, recent papers reported the possible role of microbiome composition in IPF. The roles of microbiomes in respiratory functions and as clinical biomarkers for IPF remain unknown. In this study, we aim to identify the relationship between the microbial environment in the lung and clinical findings. Methods: Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 30 publications
4
46
1
Order By: Relevance
“…Based on the reported bacterial topography data we can assume that the lung luminal and tissue-resident microbes described here have migrated primarily by microaspiration and additionally by mucosal dispersion from the upper respiratory track ( Dickson et al, 2017 ). The similar frequency of the BALF microbial communities at phylum level in healthy individuals and IPF patients between our findings and previous reports suggests that contamination was probably minimum in our present study ( Molyneaux et al, 2017 ; Takahashi et al, 2018 ). The risk of contamination of lung tissues sampled from IPF and lung cancer patients, and of the lungs excised from WT and TGF-β1 TG mice was also minimum, at least during sampling, because sampling was performed under sterile surgical conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the reported bacterial topography data we can assume that the lung luminal and tissue-resident microbes described here have migrated primarily by microaspiration and additionally by mucosal dispersion from the upper respiratory track ( Dickson et al, 2017 ). The similar frequency of the BALF microbial communities at phylum level in healthy individuals and IPF patients between our findings and previous reports suggests that contamination was probably minimum in our present study ( Molyneaux et al, 2017 ; Takahashi et al, 2018 ). The risk of contamination of lung tissues sampled from IPF and lung cancer patients, and of the lungs excised from WT and TGF-β1 TG mice was also minimum, at least during sampling, because sampling was performed under sterile surgical conditions.…”
Section: Discussionsupporting
confidence: 91%
“…A previous report showed that bacteria of the Staphylococcus and Streptococcus genera worsen the clinical outcome of IPF patients, suggesting their implication in the disease progression and pathogenesis 7 . Studies showing the relative abundance of Staphylococcus or Streptococcus genera in the fibrotic lung and its significant correlation with the host immune response in IPF patients further support the contribution of these bacteria genera in the pathogenesis of pulmonary fibrosis 6,42,[48][49][50][51][52] . However, the precise mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…Our clinical observations suggest that rapid worsening or AE of IPF are often preceded by "cold-like" symptoms without clearly establishing an acute infectious respiratory disease. Recently, several studies suggested that progression of IPF seems to be associated with bacterial or viral infection and/or abnormal composition of the lung microbiome, which is a good reason to revisit the definition of AE-IPF [3,[12][13][14][15][16][17]. Afarwal and Jindal [4] have shown that infections are able to induce an inflammatory cascade in the lung of IPF patients, thus leading to a rapid deterioration of stable IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Typical common cold symptoms include cough, worsening dyspnea and mild fever-all of them have been included in the description of AE-IPF events [11]. Further, recent evidence points towards a potential role of an altered lung microbiome in triggering IPF progression, including AE-IPF [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%